Exploring Mathematical Concepts in Batik Sidoluhur Solo - Naufal Ishartono; Dewi Ayu Ningtyas (Universitas Ahmad Dahlan, 2021)
Many ethnomathematical studies examine the existence of mathematics concepts in Indonesian cultural products where batik is one of them. However, there is a lacunae from previous studies that examine the existence of mathematical concepts in Batik Sidoluhur. Therefore, the current study aims to explore mathematical concepts in Batik Sidoluhur, such as geometry, algebra, arithmetic, and statistics. The study used ethnography as an approach by answering four principal questions, namely